PENGARUH PENGAWASAN TERHADAP EFEKTIVITAS PENGGUNAAN DANA HIBAH PETERNAKAN DAN PERIKANAN (Studi Pada Dinas Peternakan dan Perikanan Kabupaten Bandung Barat) - Asep Suhendi Arifin (JRPA - Journal of Regional Public Administration, 2017)
This research is motivated by the lack of effectiveness in the use of grants Livestock and Fisheries of West Bandung regency. The problem is assumed to be affected by not optimal supervision conducted by the Department of Animal Husbandry and Fishery West Bandung regency. Based on these problems, we propose the problem: "How much influence the effectiveness of supervision of the use of Grants Livestock and Fisheries in West Bandung regency". The theory is used to analyze the research is the theory of the supervision of Terry in the Brantas (2009: 195) states that the measurement of the supervision includes direct supervision, indirect supervision and monitoring by exception. As for measuring the effectiveness of the use theory of Duncan in Steers (1994: 16) that penapaian, integration and adaptation. Based on the theory that theory, the hypothesis is: "The magnitude Influence Usage Monitoring the Effectiveness of Grant Ranch and Livestock in West Bandung regency determined by direct supervision, indirect supervision and monitoring by exception". The method used in this research is an explanatory survey with data collection through library research and field studies through observation, interviews and questionnaires. The sampling technique used for the research was probability sampling, in particular the simple random sampling method. The design of hypothesis testing to test the influence of independent variables and the dependent variable using the method of Spearman correlation analysis. The results showed the effect of supervision of the Effectiveness of Using Grants Livestock and Fisheries in West Bandung regency is determined by the dimensions of the implementation of direct supervision, indirect supervision and monitoring by exception.